Changing from Traditional Practice to a New Model for Preparing Future Leaders - Mary Devin; Donna Augustine-Shaw; Robert F. Hachiya (Educational Considerations, 2016)
In dramatic departure from the traditional format of programs preparing building level leaders, in the last sixteen years the Educational Leadership Department in the College of Education at Kansas State University (KSU) has worked with eight different partners in designing and delivering site-based customized 30-hour master’s degree programs in educational leadership to 19 individual cohorts.
Keywords: Future Leaders; academies; positions; r leadership; Educational; University Contributions; Planning; Partnership; District Liaison